Aportacions de les altres ciències socials a la sociolingüística catalana - Vila i Moreno, F. Xavier (Caplletra. Revista Internacional de Filologia, 2004)
This article reviews the contribution of the different Catalan social sciences —excepting laws and political science— to the creation of sociolinguistics as a research field. In the conclusions it is mentioned that, in spite of the fact that research on language and society has not been an exclusive field for the linguists, and although some of the sociolinguistical disciplines have attained a great level of development, the degree of exchange between different currents and disciplines is quite limited, therefore it is preferable to speak, at most, of multirateral research, rather than of real interdisciplinarity. The article concludes that the new immigration of non-Catalan speakers makes even more necessary to fight against the isolationism of the sociolinguistical currents as well as against the lack of interest for the language shown by the Catalan social sciences.